Triggering chemical reactions by Scanning Tunneling Microscopy: From atoms to polymers. (October 2016) - den Boer, Duncan; Elemans, Johannes A.A.W.
Graphical abstract: Highlights: Chemical reactions at surfaces can be imaged at the single molecule level with STM. By applying local voltage pulses in an STM, atom-atom bonds can be broken or formed. Specific bias voltages between the STM tip and a surface can induce redox reactions. With an STM tip well-defined polymerization reactions can be triggered at a surface. Abstract: Besides its unique ability to image atoms and molecules at surfaces at unprecedented detail, a Scanning Tunneling Microscope can also be employed to manipulate matter at the nanoscale. This feature article focuses on the use of STM to induce chemical reactions at a surface, in particular involving small and larger assemblies of molecules. It will be shown that via local voltage pulses delivered by the STM tip (delivering charge carriers to the surface), by applying specific bias potentials between the STM tip and the sample, or through electrochemical control over a whole surface, a variety of chemical reactions can be induced. In this way, bonds between molecules can be broken or created, redox states can be changed, and well-defined polymerization reactions can be triggered, and the reaction components – starting materials, products, and in some cases also intermediates – can be identified in a highly appealing way: by imaging them.